Center for Community Engagement 2007 Fall Newsletter
The first semester of our new Center for Community Engagement was busy! We started the semester off with a Constitution Day (Sept. 17) debate by two CSUCI political scientists, Sean Kelly and Steve Lefevre. Each gave their view of the relevance of the constitution in our global, post-September 11 world. In October we had two events, both co-sponsored by the Political Science Program. The first was a talk about Middle East politics by Israeli journalist Yitzhak Ben-Horin. Second, co-director, Andrea Grove spoke about her new book (Political Leadership in Foreign Policy: Manipulating Support across Borders; Palgrave, 2007). Later in the semester we brought in a community group to host their meeting on campus: HIV/AIDs prevention training for practitioners. And in December we continued our participation in the American Democracy Project in meetings with faculty and administrators from local community colleges.